Nusantara Dance as a Therapeutic and Educational Medium for SLBN Bireuen Students - Novita Hidayani; Cut Santika (Universitas Negeri Medan, 2025)
This study aims to analyze the utilization of Acehnese Nusantara Dance as both a therapeutic and educational medium for children with special needs at Bireuen Special Needs School (SLB). The research was conducted using the Research and Development (R&D) method, which includes stages of problem identification, product design, development, pilot testing, and systematic evaluation. The findings indicate that dance learning significantly enhances students' motor, cognitive, social, emotional, and participatory skills. Structured evaluations show an average increase of 25% in motor skills, a 30% rise in social participation, and improved memory of movement sequences and coordination. Dance learning is also proven to be effective as a therapeutic medium, especially for deaf and intellectually disabled students, through visual cues, rhythmic music, and individualized instructions tailored to each child's needs. The final product—a performance of Acehnese Nusantara Dance—was piloted and validated by experts, receiving an average validation score of 4.2 out of 5. This research produces an inclusive learning model that not only supports students' personal and social development but also contributes to the preservation of Nusantara culture. Thus, this approach provides an innovative solution to improve the quality of education and therapy for children with special needs in the SLB environment.